2018
DOI: 10.1055/a-0646-3803
|View full text |Cite|
|
Sign up to set email alerts
|

In vivo Evaluation of Anti-Hyperglycemic, Anti-hyperlipidemic and Anti-Oxidant Status of Liver and Kidney of Thymol in STZ-Induced Diabetic Rats

Abstract: The results of this research has brough a new aspect concerning the proteevtive and positive effects of thymol on the diabetic complications in the animal model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 29 publications
3
12
0
Order By: Relevance
“…Also, the results from this study showed that in the groups treated with thymol and thymol nano polymer, as with the diabetic group treated with glibenclamide, serum insulin levels significantly increased compared to the diabetic group. Previous studies, in confirmation of our study, have shown that increase blood glucose levels and decrease insulin levels in STZ diabetic rats, confirmed that hyperglycemia is a main cause for disruption of insulin in the optimal rate [16,41,42] Moreover, in one research treatment by thymol led to a significant reduces in the blood glucose level and increase in serum insulin level after 28 d in the STZinduced diabetic rats [48]. However, the anti-diabetic mechanism of thymol, which is responsible for increasing the rate of serum insulin secretion and decreasing of blood glucose, is still unclear [42].…”
supporting
confidence: 90%
See 1 more Smart Citation
“…Also, the results from this study showed that in the groups treated with thymol and thymol nano polymer, as with the diabetic group treated with glibenclamide, serum insulin levels significantly increased compared to the diabetic group. Previous studies, in confirmation of our study, have shown that increase blood glucose levels and decrease insulin levels in STZ diabetic rats, confirmed that hyperglycemia is a main cause for disruption of insulin in the optimal rate [16,41,42] Moreover, in one research treatment by thymol led to a significant reduces in the blood glucose level and increase in serum insulin level after 28 d in the STZinduced diabetic rats [48]. However, the anti-diabetic mechanism of thymol, which is responsible for increasing the rate of serum insulin secretion and decreasing of blood glucose, is still unclear [42].…”
supporting
confidence: 90%
“…ALT and AST are the important hepatic enzymes due to their levels in serum as the specific and reliable biomarker for liver damages [42,49,50]. In confirmation of our results, it was shown in a paper that thymol 40 mg/kg has been able to significantly reduce ALT and AST in diabetic rats by STZ and help animal health [48]. It has been documented that the Zataria multiflora essential oil has been able to protect the increase of ALP produced by STZ in diabetic rats [51].…”
supporting
confidence: 82%
“…The difference test between groups was performed by one-way ANOVA, be continued using post hoc Tukey. The one-way analysis of variance (ANOVA) is used to evaluate if there are any statistically significant discrepancies between the means of two or more distinct (unrelated) groups [15,16].…”
Section: Discussionmentioning
confidence: 99%
“…The SPSS package (version 16) was applied in statistical analysis. The comparison between groups was performed by one-way ANOVA, followed by post hoc Tukey [15,16].…”
Section: Discussionmentioning
confidence: 99%